Design and evaluation of a mechanical pencil-based actuator for a wasp-inspired needle - Jette Bloemberg; Mario van der Wel; Aimée Sakes; Paul Breedveld (PLoS ONE, 2025)
In percutaneous interventions, long and thin needles are used to reach deep target locations within the body. However, inserting a long and thin needle into the tissue can cause needle buckling, resulting in poor control of the needle’s trajectory and reduced targeting accuracy. In nature, the female parasitic wasp prevents the buckling of her long and slender ovipositor through a self-propelled motion. This study presents a stationary actuation system that can advance a wasp-inspired self-propelled needle consisting of seven 0.3-mm stainless steel rods with a theoretically unlimited insertion length. Based on the pencil lead advance mechanism in mechanical pencils that advances the pencil lead at a fixed increment when the pencil button is pushed, our actuation system advances the seven needle segments that comprise our needle by locking, advancing, releasing, and retracting the advance mechanisms. Experimental evaluation demonstrated that the actuation system successfully executes these actions, enabling step-by-step propulsion of the needle segments in gelatin-based tissue-mimicking phantoms. Moreover, the needle achieved mean motion efficiencies of 98 ± 2%, 68 ± 5%, and 57 ± 7% in air, 5-wt% gelatin, and 10-wt% gelatin, respectively, over 15 actuation cycles. This actuation system prototype, which is based on a mechanical pencil, is a step forward in developing self-propelled needles for targeting deep tissue structures.